2015
DOI: 10.1177/2156587214564188
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Benefits of Satureja Species on Metabolic Syndrome and Their Possible Mechanisms of Action

Abstract: Metabolic syndrome, also known as insulin resistance disorder, is the simultaneous manifestation of multiple metabolic disorders in an individual. The present-day complementary and alternative therapies suggest several medicinal herbs that may have the potential to improve one or multiple complications of metabolic syndrome. All of them have their own limitations in efficacy and unwanted effects. Therefore, we reviewed species of Satureja as widespread medicinal herbs and potentially good remedies for metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…The study results revealed the effectiveness of using S. hortensis for treating some metabolic syndrome symptoms. Different studies on Satureja species have also shown their efficacy for treatments of metabolic disorders (4)(5)(6)(7)(8)(11)(12)(13)(14)(15)(16)(17). The following discussion includes the substantiated mechanisms involved in the pathogenesis of metabolic syndrome's main concomitant disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results revealed the effectiveness of using S. hortensis for treating some metabolic syndrome symptoms. Different studies on Satureja species have also shown their efficacy for treatments of metabolic disorders (4)(5)(6)(7)(8)(11)(12)(13)(14)(15)(16)(17). The following discussion includes the substantiated mechanisms involved in the pathogenesis of metabolic syndrome's main concomitant disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the impacts of Satureja species on specific symptoms of metabolic syndrome (14). Dorman and Hiltunen (2004) used an in vitro study to find that the dried crude extract of S. hortensis exhibited antioxidant and hydroxyl radical scavenging properties (5).…”
Section: Introductionmentioning
confidence: 99%
“…A work conducted in Morocco on the S. calamintha EO showed the scavenging capacity of DPPH (22.01 ± 3.13%) [31]. Babajafari et al [5] revealed that different species of Satureja exert antioxidant, lipid peroxidation-inhibiting and anti-inflammatory activities. In addition, Bouzidi et al [7] showed that S. calamintha oil has a significant effect on the inhibition of the free radicals produced by DPPH with an IC 50 of 31.25 µg/mL.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Satureja extracts have been reported to possess various therapeutic effects. In addition, this plant possesses antiseptic, antioxidant, antibacterial, antifungal, antidiarrheal, anti-inflammatory, and antispasmodic properties [5]. S. calamintha is very popular in Morocco and Algeria, where it is used as an odoriferous agent in perfumes and as a powerful disinfectant [6].…”
Section: Introductionmentioning
confidence: 99%
“…Satureja is used in meals for flavouring and as a folk remedy for treating various symptom conditions, for instance, infectious diseases, indigestion, diarrhoea, cramps, nausea, and muscle pains (Sefidkon & Emami‐Bistgani, 2021). Recent phytochemical research found the presence of flavonoids such as apigenin, luteolin, diosmetin, naringenin, taxifolin, aromadendrin, eriodictyol, and phenolic acids such as labiatic acid, carvacrol and thymol in the aerial parts of Satureja (Babajafari et al ., 2015). Carvacrol, cymene, terpinene, pinene, myrcene, thymol, linalool, and caryophyllene are the primary ingredients of Satureja (Maccelli et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%